2018
DOI: 10.1111/nyas.13657
|View full text |Cite
|
Sign up to set email alerts
|

Short bowel syndrome: influence of nutritional therapy and incretin GLP1 on bone marrow adipose tissue

Abstract: Energy deprivation leads to a decrease in white adipose tissue and bone mineral density (BMD), while simultaneously inducing the expansion of marrow adipose tissue (MAT). In short bowel syndrome (SBS), parenteral nutrition mitigates the deterioration of nutritional status, including decreases in MAT. Osteoporosis is, however, a frequent complication of SBS. The objective of our study here was to evaluate the association of fat deposit sites (subcutaneous and visceral adipose tissues: intrahepatic lipid (IHL) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…There is evidence suggesting that GLP1 and GIP both stimulate bone formation 29 . A recent study observed that the serum levels of GLP1 have a positive relationship with MAT in individuals with SBS and that the circulatory levels of GIP are positively correlated with total hip BMD in normal patients 21 . Herein, the follow‐up of SBS individuals showed that the serum levels of GIP were greater in the latter determination than in the former, indicating the improvement in intestine adaptation.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…There is evidence suggesting that GLP1 and GIP both stimulate bone formation 29 . A recent study observed that the serum levels of GLP1 have a positive relationship with MAT in individuals with SBS and that the circulatory levels of GIP are positively correlated with total hip BMD in normal patients 21 . Herein, the follow‐up of SBS individuals showed that the serum levels of GIP were greater in the latter determination than in the former, indicating the improvement in intestine adaptation.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, there is a negative relationship between bone mass and MAT, supporting the tenet that adipogenesis in bone marrow occurs at the expense of bone formation 33 . A recent study showed that, unlike women with active anorexia nervosa, SBS patients receiving either parenteral or oral nutrition show both normal amounts of MAT and a positive relationship between MAT and bone mass 21 . Herein, it was observed that the SBSG, with a postsurgery mean time of 6 years, exhibited unchanged MAT and BMD after 1 year of subsequent follow‐up.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Insulin resistance and its related disorder, nonalcoholic fatty liver disease (NAFLD), are two of the most common and severe complications associated with obesity. According to previous studies, hepatic accumulation of fat is negatively associated with bone mass in individuals with short bowel syndrome ( 22 , 23 ). However, studies evaluating the association of NAFLD and bone in individuals with obesity and T2DM have shown conflicting results, suggesting that factors other than the amount of intrahepatic lipids (IHL) mediate the relationship between liver and bone ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 90%
“…[15] The interaction between adipose tissue and the skeleton has an additional ingredient, as special adipocytes within marrow adipose tissue (MAT) are part of the universe of cells composing the bone marrow. MAT, at least in humans, shows crucial adaptive differences in response to nutritional fluctuations by expanding during periods of calorie restriction while appearing not to be a site for fat storage during calorie surplus [13, 16, 17]. Previous studies show that MAT expands in patients with autoimmune diseases submitted to glucocorticoid therapy, as well as in individuals diagnosed with CD [15, 18].…”
Section: Introductionmentioning
confidence: 99%